Classroom management into learning: using phenomenography to analyse student teachers' conceptions of classroom management - Ana Maria Correia (Universidade Católica Portuguesa, 2019)
Classroom management is a critical area in the curriculum of teacher education programs. Student teachers' conceptions of the role of the teacher as a class leader are frequently backed by their intuition and experience as students and socio-cultural context rather than evidence-based. This paper examines the conceptions of classroom management held by a multicultural group of forty-four student teachers attending a teacher education program at a higher education institute in Macao. The study aims at understanding the patterns of variation expressed by student teachers regarding the purpose and relevance of the object of learning. It compares a) the patterns of variation in students' views of classroom management, and b) the students' learning progress based on the pre-and post-test. The phenomenographic approach was adopted as the conceptual framework. Participants handwritten transcripts from student teachers at the first and last sessions of the course are the primary type of data collection. The findings show that changes in student teachers' understanding of the conceptions of classroom management occurred during the course. The initial preferences for disciplinary approaches to classroom leadership have given way to conceptions of promoting the integration of classroom management into learning. The participants expressed increasing adherence to classroom management systems targeting and providing behavioural and academic supports and interventions to children and adolescents with and without special needs.